Knowing more from less: miniaturization of ligand-binding assays and electrophoresis as new paradigms for at-line monitoring and control of mammalian cell bioprocesses. (October 2021) - Pinto, Inês F; Mikkonen, Saara; Josefsson, Leila; Mäkinen, Meeri E-L; Soares, Ruben RG; Russom, Aman; Emmer, Åsa; Chotteau, Veronique
Graphical abstract: Highlights: Microfluidic devices enable fully automated and integrated at-line monitoring systems. Microchip capillary electrophoresis is a promising tool for bioprocess monitoring. Microfluidic affinity assays can be used for detection of bioprocess target proteins. Miniaturization enables PAT at reduced cost and without need of complex instruments. Monitoring technologies for Process Analytical Technology (PAT) in mammalian cell cultures are often focusing on the same hand full parameters although a deeper knowledge and control of a larger panel of culture components would highly benefit process optimization, control and robustness. This short review highlights key advances in microfluidic affinity assays and microchip capillary electrophoresis (MCE). Aiming at the miniaturization and integration of PAT, these can detect at-line a variety of metabolites, proteins and Critical Quality Attributes (CQA's) in a bioprocess. Furthermore, discrete analytical components, which can potentially support the translation of increasingly mature microfluidic technologies towards this novel application, are also presented as a comprehensive toolbox ranging from sample preparation to signal acquisition.